But i don't have customer - Coastal Training Technologies ([Virginia Beach, Va.] : Coastal Training Technologies, Coastal AMI, 2004)
Program teaches your employees to respect internal customers as if they were paying clients. By asking questions, listening and keeping their word, your employees can create a positive and productive work environment, which will inevitably reflect on your external customers as well. Includes interactive training scenes, training points, quiz, printable leader's guide, and customizable Power-Point presentation.
DVD format
Optional language in English, Espanol and Portuguese
Keywords: Office practice in government; Interpersonal relations; Employee motivation; Organizational behavior